2001
DOI: 10.1038/eye.2001.153
|View full text |Cite
|
Sign up to set email alerts
|

Is the role of trabeculectomy in glaucoma management changing?

Abstract: Background In recent years there have been significant developments in the diagnosis and treatment of glaucoma. We conducted a study to determine whether there has been an associated change in trabeculectomy rates in England over this period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 11 publications
0
21
0
Order By: Relevance
“…The issues of surgical exposure and learning effects have been discussed recently in the context of the declining numbers of glaucoma operations. 25 The UK National Trabeculectomy Study 26 highlights the importance of adequate supervision and training. Nonconsultant career grade surgeons achieved lower success rate than other surgeons groups, but no difference was found between junior ophthalmology trainees and fully qualified surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…The issues of surgical exposure and learning effects have been discussed recently in the context of the declining numbers of glaucoma operations. 25 The UK National Trabeculectomy Study 26 highlights the importance of adequate supervision and training. Nonconsultant career grade surgeons achieved lower success rate than other surgeons groups, but no difference was found between junior ophthalmology trainees and fully qualified surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10] Similarly, two studies have reported reductions in the total number of patients undergoing trabeculectomy in England over the past decade. 11,12 Whittaker et al 11 showed from Hospital Episode Statistics (HES, described below) that the annual number of patients undergoing trabeculectomy in England increased year on year from 10 115 (1989-1990) to 18 928 (1995-1996), then decreased year on year to 14 507 (1997-1998). More recently, Fraser et al 12 used HES data collected in a newer format to show that the annual number of patients undergoing trabeculectomy decreased year on year from 8622 (1998-9) to 4206 (2003-4).…”
Section: Introductionmentioning
confidence: 99%
“…4 As a result, over the same period there has been a steady decline in the number of trabeculectomies being performed. 4,5 This is occurring during a time when higher surgical trainees (HST) are expected to perform a set number of glaucoma procedures. 6 The use of antimetabolites intraand postoperatively has increased considerably since 1996 with more aggressive postoperative management of the failed trabeculectomy bleb.…”
Section: Introductionmentioning
confidence: 99%